Epistemologias e descolonização na América Latina: compreendendo as mediações e a transmetodologia como práxis epistêmico-metodológicas transformadoras - Santos Vieira, Eloy (2020)
DOI: 10.26439/contratexto2020.n033.4791 Our central argument in this paper is that we need a decolonized perspective for Communication in Latin America. Thus, we propose points to discuss about other epistemologies and methodologies that emerge from original and autochthonous realities from concrete contexts that affect us, but which are not always observed by appropriate criteria to our history and our empirical reality. Therefore, we intend to emphasize the surrounding social processes over restricted bipolar perspectives that only recognize reception and/or production. In addition, we also make some theoretical approaches and confrontations about the construction of Western Thinking and its epistemologies and then discuss the constitution of Social Sciences and Communication as a field and its trajectory within Latin America. In the end, we also suggest an approximation from proposals to operationalize the mediations and the transmethodological perspective that constitute two powerful ways to think concretely about the methodological configurations from Latin America.